2019
DOI: 10.21203/rs.2.14900/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with unintended pregnancy in Ethiopia; further analysis of the 2016 Ethiopian demographic health survey data.

Abstract: Background Unintended pregnancy is an important public health problem in Ethiopia. It causes adverse physical, mental, social and economic outcomes. Identifying factors associated with unintended pregnancy may help to reduce unintended pregnancy and hence adverse outcomes. There are few studies about the prevalence and associated factors of unintended pregnancy in Ethiopia. But these studies were based on few sample size and fragmented. Therefore, this analysis was done to identify factors associated with uni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(45 reference statements)
2
2
0
Order By: Relevance
“…Furthermore, another finding revealed that more than half of pregnant women had three and more parities. This finding was in agreement with Bekele, [17] who found that increased parity more than were more likely to have unintended pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, another finding revealed that more than half of pregnant women had three and more parities. This finding was in agreement with Bekele, [17] who found that increased parity more than were more likely to have unintended pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies in agreement with the current study finding who found that contraceptive failure was the major reason for UP followed by not using FP for mistimed pregnancy. [17] The present finding revealed that contraceptive failure was the main reason for UP. Most of the failure rate was due to using pill either combined or progesterone only, followed by intrauterine devices, natural methods, injectable, chemical and barrier methods.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations